Modelling the effect of betel leaf essential oil on germination time of Aspergillus flavus and Penicillium expansum spore population. (September 2018) - Basak, Suradeep
Abstract: The objective of this study was to model the efficacy of betel leaf ( Piper betle L.) essential oil (BLEO) on germination of Aspergillus flavus and Penicillium expansum spore population. Experimental data of rate of spore germination under the influence of the range (0.1–1.5 μl/ml) of BLEO concentration were fitted to the asymmetric model, and the germination time parameter was estimated with satisfactory statistical indices (RMSE and R 2 ). The secondary modelling of germination time as a function of BLEO using the reciprocal of re-parameterized Monod-type equation estimated minimum inhibitory concentration 0.65 and 0.54 μl/ml of BLEO for spore germination of A. flavus and P. expansum, respectively. The accuracy and bias factor of the fitted secondary model suggested good similarity between observed and estimated germination time values under the influence of BLEO for both selected moulds. It can be concluded that the asymmetric model and the re-parameterized Monod-type model could describe the inhibitory pattern of the essential oil against two selected predominant food spoilage moulds. The antifungal activity also suggests the potential of BLEO as natural antimicrobials. Highlights: Asymmetric model estimated spore germination time under the influence of BLEO. Variance of estimated germination time was stabilized by square-root transformation. A f and B f showed the plausibility of the secondary model in estimating MIC of BLEO. Predictive mycological tools can describe spore germination under influence of EOs.